Applicable Law on Electronic Arbitration Procedures - A Comparative Study- - Hassan, Mohammad Jalal; Rahim, Bakhtyar Sidiq (Journal of Legal and Political Studies, 2019)
The procedures which applied to electronic arbitration are important in the arbitration which is no less important than the substantive aspect of the arbitration, from how the proceedings proceed to the manner in which the judgment is rendered, because of its importance related to arbitration and its consequences in terms of validity and invalidity. The existence of any legal defect in the proceedings may end the process and endanger the risk of non-compliance. The importance of these procedures is also demonstrated by the law applied by the arbitral tribunal to these procedures, whether the arbitration is free or institutional, which may be conflicts appear in the laws that can be taken and the process of proceeding according to them, through the application of the law of will chose by the parties to arbitration. In accordance with the principle of the will of the will and the absolute freedom of the parties to determine the law they wish to proceed in order, or to proceed execute the law of the State on whose territory the arbitration procedure is conducted, t is often done in a free arbitration, which The arbitrator or the arbitral tribunal does not have its own internal regulations and rules. It is composed of a group of experienced arbitrators, who have been selected and elected for specific disputes only, or through the application of the law chosen by the arbitral tribunal through the lists of arbitral centers from which arbitration bodies have arisen if the parties have not expressly declared selected law.
Keywords: electronic arbitration; proceedings; noncompliance; arbitral tribunal; arbitration bodies